What I Learned about AfricanAmericans - Foster, Douglas A. (Stone-Campbell journal, 2013)
Focusing on Preston Taylor, Samuel R. Cassius, Sara Lue Bostick, and Annie Tuggle, Foster provides a glimpse into the complexities of race, culture, and theology experienced by these black leaders from the time of American slavery to the civil rights movement. The paper was drawn from material written by Lawrence A. Q. Burnley, Edward Robinson, and Douglas A. Foster and published in The Stone-Campbell Movement: A Global History (Chalice, 2013).